Digital Public Relations Strategies on Instagram in Promoting Environmental Sustainability: Content Analysis of @nucare_lazisnu - Abiyyu Dzikri Al-Hamdi; Iman Sumarlan (Electronic Journal of Education, Social Economics and Technology, 2026)
This study examines digital public relations strategies employed through Instagram in promoting environmental sustainability, focusing on the official account of NU Care-LAZISNU, @nucare_lazisnu. Using a qualitative research design, the study applies descriptive thematic content analysis to Instagram posts related to environmental sustainability published over a defined period. The analysis reveals that sustainability communication is predominantly oriented toward informational and educational messages, supported by visual storytelling that enhances message clarity and public awareness. Image-building strategies play a significant role in integrating environmental sustainability into the organization’s humanitarian identity, thereby strengthening organizational credibility and public trust. Persuasive messages and explicit calls to action generate higher levels of audience engagement, indicating the importance of participatory communication in sustainability campaigns. However, the findings also show limited dialogic interaction, suggesting that Instagram is primarily utilized as a one-way communication channel rather than a fully interactive public relations platform. This study contributes to the literature on digital public relations and environmental communication by providing empirical evidence from a non-profit, faith-based organizational context in a developing country. The findings offer practical insights for organizations seeking to enhance the effectiveness of sustainability communication through social media.